The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/bi9003638
|View full text |Cite
|
Sign up to set email alerts
|

The M17 Leucine Aminopeptidase of the Malaria Parasite Plasmodium falciparum: Importance of Active Site Metal Ions in the Binding of Substrates and Inhibitors

Abstract: The M17 leucine aminopeptidase of the intraerythrocytic stages of the malaria parasite Plasmodium falciparum (PfLAP) plays a role in releasing amino acids from host hemoglobin that are used for parasite protein synthesis, growth, and development. This enzyme represents a target at which new antimalarials could be designed since metalloaminopeptidase inhibitors prevent the growth of the parasites in vitro and in vivo. A study on the metal ion binding characteristics of recombinant P. falciparum M17 leucine amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 39 publications
3
47
0
Order By: Relevance
“…Our biochemical studies suggest that the ability of Pf A-M17 to rapidly gain or lose a divalent cation, most likely at the regulatory site 1, may represent an important mechanism of regulation of catalytic activity not only for the binding of substrates but also inhibitors (13). Consistent with this idea, we found that in the absence of environmental metal, no metal ion was observed at the catalytic site 1 position (SI Text Fig.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Our biochemical studies suggest that the ability of Pf A-M17 to rapidly gain or lose a divalent cation, most likely at the regulatory site 1, may represent an important mechanism of regulation of catalytic activity not only for the binding of substrates but also inhibitors (13). Consistent with this idea, we found that in the absence of environmental metal, no metal ion was observed at the catalytic site 1 position (SI Text Fig.…”
Section: Resultssupporting
confidence: 79%
“…In contrast, the second metal ion is "tightbinding" and is known as the catalytic site 2 (18). Metal replacement studies on Pf A-M17 show that the enzyme retains activity when only the tight-binding catalytic site 2 is occupied with a metal ion; removal of both metal ions lead to complete and irreversible inactivity (7,13). Consistent with these ideas, in the presence of increasing concentrations of EDTA, loss of M17 activity follows a biphasic pattern as each metal ion is sequentially chelated (13) (SI Text Fig.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Modulation of the proteolytic activity of IDE could therefore occur through different routes such as coordination of exogenous ligands to the catalytic metal, substitution or removal of the latter [44][45][46][47][48][49][50][51]. Moreover, metals could bind either to residues present in the active site to block substrate interaction or to residues outside the active-site to affect the structural integrity of the enzyme [42,43]; iii.…”
Section: Introductionmentioning
confidence: 99%